DAMPAK KEBIJAKAN SERTIFIKASI TERHADAP KINERJA GURU DISEKOLAH MENENGAH SE KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI - Yelni, Muhlina; Syahza, Almasdi; Hendripides, Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the impact of certification policy on the performance of middle school teachers throughout the district across the downstream districts kuantanSingingiKuantan. The population in this study amounted to 65 with a sample of 31 people. The type of data used in this study are primary and secondary data. The collected data is then analyzed using normality test and test different T with SPSS. This study proves that there is a certification policy impact on the performance of middle school teachers throughout kuantan downstream districts across KuantanSingingi where the average performance of teachers who have been certified higher than the average performance of teachers who have not been certified. The study recommended for teachers who have not been certified to be more motivated to perform better and improve the performance shown to prove that teachers are not certified does not necessarily have a lower performance compared to teachers who have been certified and able to compete with teachers who have been certified in improving the quality of produced by training, upgrading and adding media information.Keywords: Certification Policy, TeacherPerformance.